SEVERE POSTDURAL PUNCTURE HEADACHE: CASE OF PRACTICE - Negrych, T. I.; Kyryliuk, S. Ya.; Bozhenko, M. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Headache is one of the most common complications after lumbal punction or epidural anesthesia. The article presents a clinical case of post dural puncture headache in a 26-year-old woman, 25 days long. An intracranial hypotension was confirmed by the help of magnetic resonance imaging of the brain, a pituitary gland with a slightly convex upper contour and a rounded form of transverse venous sinus were found. Positive effect of rehidratation, analgesics, non-steroid anti-inflammatory and antiemetic drugs and drugs of caffeine in the treatment of post-dural puncture headache was noted.